PEMANFAATAN MEDIA SOSIAL DALAM PENYULUHAN PENCEGAHAN PENULARAN COVID-19 PADA MASYARAKAT - Wijaya, Liza (ABDIMAS Madani, 2022)
COVID-19 has become a global pandemic that has hited more than 200 countries, including Indonesia. The soaring number of COVID-19 cases has forced the government to re-impose large-scale restrictions and several health protocols. However, there are many factors that influence people's behavior related to health. One of them is the lack of correct information and education in changing risky behavior. Social media of instagram is one of the educational media and information delivery that can be accessed easily and has various features. This community service activity aims to provide knowledge in preventing the transmission of COVID-19 by implementing health protocols. The method used in this activity is counseling on the prevention of Covid-19 transmission by displaying infographic videos. The results of this activity can illustrate use of social media in delivery of effective and efficient education and is expected to increase public knowledge in preventing the transmission of COVID-19.